12x-3y=-36

Simple and best practice solution for 12x-3y=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3y=-36 equation:


Simplifying
12x + -3y = -36

Solving
12x + -3y = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
12x + -3y + 3y = -36 + 3y

Combine like terms: -3y + 3y = 0
12x + 0 = -36 + 3y
12x = -36 + 3y

Divide each side by '12'.
x = -3 + 0.25y

Simplifying
x = -3 + 0.25y

See similar equations:

| (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 | | 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) | | 3(-0.8+0.4y)+2y=0 | | (7r-4)(r+5)-(2r-1)(r+5)= | | 2(3y+7)=44 | | (3x+1)+(8x-24)= | | 0=.333x+4 | | -y^2=0 | | 14u-9u=45 | | 13=y+20 | | 3(-5+5x)-2x=11 | | t^2-2t=(t+3) | | 5+4w=-3 | | -3(w+4)=3w-30 | | 8+3x=19+x | | U-184=39 | | D/-2=36 | | 10(x-2)+8=12 | | 2x+2(x-5)=38 | | 4(x-8)-6x=-12 | | z^7+5z^6=0 |

Equations solver categories